Decomposition of airflow over topography and its application to a topographic blizzard event in central Asia - Ma, Shuping; Cai, Ren; Ran, Lingkun; Jiao, Baofeng; Zhou, Kuo; Guo, Anboyu (Frontiers in Earth Science, 2023)
With the aim to seize the triggering issues of extreme precipitation in Central Asia due to complicated terrains, a topographic blizzard that occurred in Xinjiang Province is selected and the near-surface wind field is decomposed into flow-around and flow-over components to analyze the dynamic and thermodynamic effects of flow around and over topography when the blizzard was triggered on November 30, 2018 in the topography of the Ili River valley and the northern slope of the Tianshan Mountains. The results show that the flow around topography is the main flow-field component that transports water vapor and causes moisture convergence. The symmetric instability at the lower level of the snowfall area is caused by the vertical shear of the flow-around wind field, the advective transport of generalized potential temperature caused by the vertical shear of the flow-around wind causes the change of the potential vorticity, thereby causing the symmetric instability. The obvious local variation of stratified instability in the snowfall area is caused by flow-over potential divergence, the advection of the flow-over wind vertical shear to equivalent potential temperature causes the change of flow-over potential divergence, thus promotes stratified instability. At the same time, the flow-over potential divergence is negatively correlated with the amount of topographic snowfall to a certain extent, which can provide reference for topographic snowfall forecast in the future. In addition, the cyclonic vorticity in the snowfall area is mainly caused by the flow around topography and flow-around wind produces favorable vortical circulation conditions for snowfall, while the vertical movement near the ground at the snowfall triggering stage is mainly caused by the flow-over component. Furthermore, the flow-over kinetic energy in the snow area is stronger and the work done by the pressure gradient force caused by flow over terrain drives kinetic energy changes.